Concept of a thin film memory transistor based on ZnO nanoparticles insulated by a ligand shell - Hirschmann, Johannes; Faber, Hendrik; Halik, Marcus (Nanoscale, 2012)

Impact of oxygen plasma treatment on the device performance of zinc oxide nanoparticle based thin-film transistors - Halik, Marcus; Peukert, Wolfgang; Braunschweig, Björn; Klaumünzer, Martin; Hirschmann, Johannes; Faber, Hendrik (ACS Applied Materials and Interfaces, 2012)
Thin-films of zinc oxide nanoparticles were investigated by photoluminescence spectroscopy and a broad defect-related yellow-green emission was observed. Oxygen plasma treatment was applied in order to reduce the number of defects, and the emission intensity was quenched to 4% of the initial value. Thin-film transistors that incorporate the nanoparticles as active semiconducting layers show an improved device performance after oxygen plasma treatment. The maximum drain current and the charge carrier mobility increased more than 1 order of magnitude up to a nominal value of 23 cm2 V−1 s−1 and the threshold voltage was lowered.
Keywords: nanoparticles; Plasma treatment; thin-film transistors; zinc oxide